IDENTIFIKASI KARAKTERISTIK KERBAU BELANG YANG MENENTUKAN HARGA JUAL TERTINGGI DI PASAR HEWAN BOLU KABUPATEN TORAJA UTARA - Ikrar Mohammad Saleh; Aslina Asnawai (State Islamic University (UIN) Alauddin, 2014)
ABSTRACT.This study aims to investigate the characteristics of Tedong Bonga that determine it’s prices in the Market Animal Bolu North Toraja Regency. The research was conducted for approximately one month starting from the month of May to June 2013 in the Market Animal Bolu, District Tallunglipu, North Toraja Regency. Type of research was descriptive quantitative with Deplhi methods. This type of data wass qualitative and quantitative. Sources of data are primary and secondary data. The results indicate characteristic stripes that the highest selling price in the Market Animal striped buffalo Bolu.